Language Education and the Construction of Cultural Identity: A Comparative Analysis of National Language Policies in Indonesia and Malaysia in the Era of Globalization - Khodijah; Suci Dwina Darma (Jurnal Ilmiah Multidisiplin Keilmuan Mandira Cendikia, 2026)
Language education serves as a strategic instrument in shaping cultural and national identity, particularly in multi-ethnic nations such as Indonesia and Malaysia. Utilizing a qualitative approach based on literature review, this article analyzes the contribution of language education to the construction of cultural identity in both countries. The theoretical framework encompasses Language Policy and Planning (Spolsky, 2004) and Language Ideology (Woolard, 1998). Findings indicate that Indonesia develops an integrative-pluralist model through the assertion of Bahasa Indonesia as a national unifier, while Malaysia implements an ethno-national orientation in language education with Bahasa Melayu as a symbol of majority identity. Despite sharing Malay linguistic roots, historical politics and social dynamics have shaped ideological differences in language education. This study also identifies research gaps in comparative language education policy studies that integrate globalization dynamics and multilingual realities within the ASEAN context. The article contributes to understanding how postcolonial nations navigate the tension between national unity, ethnic diversity, and global competitiveness through language education policies.